Representasi Perlindungan Data Pribadi pada Iklan Apple Versi ‘Privacy on Iphone – Data Auction’ di Youtube : Analisis Semiotika Roland Barthes - Mohammad Ya’isy Ghifari; Oktaviana Purnamasari; Daniel Handoko (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
In this research, a semiotic analysis of the Apple commercial version of "Privacy on iPhone - Data Auction" is carried out using the Roland Barthes model. Also this research uses descriptive qualitative methods with data collection techniques of interviews and documentation studies. The purpose of this research is to find out the representation of personal data protection in the advertisement by analyzing the meaning of denotation, connotation and myth. The results of the analysis show that this advertisement clearly illustrates the risks that will occur to the personal data of smartphone owners and users if the data can be accessed easily by irresponsible parties. This commercial also proves the truth of the myth widely circulated in society that Apple devices are more secure than other brands. Apple wants to emphasize that they attach great importance to and care about the confidentiality and security of the personal data of Apple users. Therefore, Apple strives to provide security guarantees and personal data protection on its products so that Apple customers feel comfortable and confident that their data is safe.